Analysing the change in water quality parameters along river Ganga at Varanasi, Mirzapur and Ghazipur using Sentinel-2 and Landsat-8 satellite data during pre-lockdown, lockdown and post-lockdown associated with COVID-19 - Das N.; Bhattacharjee R.; Choubey A.; Agnihotri A.K.; Ohri A.; Gaur S. (My University, 2025)
Abstract: The proper functioning of the river ecosystem has been symbolised by healthy aquatic life. The river Ganga has shown signs of rejuvenation due to lockdown. In this study, an attempt has been made to analyse the change in river water quality using Sentinel-2 and Landsat-8 imageries. The quantitative analysis has been performed for temperature and normalised difference turbidity index (NDTI). The qualitative analysis has been performed for pH, dissolved oxygen (DO) and total suspended solids (TSSs). Ghazipur, Varanasi and Mirzapur stretches have been selected for this study. In the Ghazipur stretch, the river temperature decreased by 7.14% in May 2020 (lockdown period) as compared to May 2019 (1 year before lockdown). Similarly, in the Varanasi stretch, this decrease has been by 8.62%, and in the Mirzapur stretch, this decrease has been by 12.06% in May 2020 compared to May 2019. For the same period, NDTI in the Ghazipur, Varanasi and Mirzapur stretch has been decreased by 0.22, 0.26 and 0.24, respectively. The pH and DO of the river increased, and TSS decreased for the considered time period. The lockdown during the second wave of the coronavirus disease 2019 was not helpful for river rejuvenation. This study elicited how the behaviour of the parameters changed during the lockdown. Research highlights: River Ganga becomes much cleaner in the lockdown period (May 2020) compared to the pre-lockdown time.In the Mirzapur stretch, the temperature decreased most in May 2020 as compared to May 2019.In the Varanasi stretch, there is a maximum variation in the NDTI value in May 2020 in comparison with that of May 2019.The most significant task will be to maintain river conditions during post-lockdown similar to that prevailed during lockdown.In the second wave COVID-19 lockdown the river again became polluted like the pre-COVID times. © 2022, Indian Academy of Sciences.